2019
DOI: 10.1055/s-0039-1677777
|View full text |Cite
|
Sign up to set email alerts
|

Antegonial Notch and Mandibular Symphysis as indicators of Growth Pattern

Abstract: IntroductionThe knowledge of the nature and magnitude of growth and development of human face is important for sound diagnosis and treatment of dentofacial disharmonies. The depth of antegonial notch and morphology of mandible are important indicators of growth pattern. Objective The purpose of this study was to evaluate the antegonial notch depth, mandibular symphysis morphology, and symphysis inclination in various facial types categorized into the normo-, hypo-, and hyperdivergent groups using various param… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Similarly, Tomer and Kishnani [19] found no significant correlation between the craniofacial morphology and the antegonial notch depth. In contrast, Kar et al [2] and Basha et al [20] evaluated the correlation of the antegonial notch depth and facial height. They categorized the patients into three groups of normal, hyperdivergent, and hypodivergent based on the Jarabak index.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Tomer and Kishnani [19] found no significant correlation between the craniofacial morphology and the antegonial notch depth. In contrast, Kar et al [2] and Basha et al [20] evaluated the correlation of the antegonial notch depth and facial height. They categorized the patients into three groups of normal, hyperdivergent, and hypodivergent based on the Jarabak index.…”
Section: Discussionmentioning
confidence: 99%
“…Finding a precise, valid, and reliable technique for mandibular growth prediction is imperative for orthodontists. Mandibular growth prediction in the early stages of life can greatly aid in more accurate diagnoses and precise treatment planning [2].…”
Section: Introductionmentioning
confidence: 99%
“…The thick symphysis is noted in a horizontal growth pattern (Ricketts, 1960). Gracco et al showed that symphysis thickness was greater in short-faced subjects than in long-faced subjects (Gracco et al, 2010).In patients with horizontal growth pattern, short symphysis height, large symphyseal depth, and the small symphyseal ratio are noted as compared with the hyperdivergent group the results were statistically signi icant but larger symphysis angle showed not a statistically signi icant difference compared to hyperdivergent group (Kar et al, 2018). Sassouni and Nanda (Sassouni and Nanda, 1964) and Bjork (Björk, 1969) have found pronounced apposition beneath the symphysis with a concavity in the inferior border of the mandible associated with the tendency toward backward jaw rotation of the mandible.…”
Section: Symphysis Width and Symphysis Anglementioning
confidence: 98%
“…This results in formation of notch at lower border of mandible which is known as pregonial or antegonial notching. [8][9][10] Patients with deep antegonial notching are found to have disturbances of condylar and mandibular growth and it is more common with the patients having vertical growth pattern. [11][12][13] Shallow antegonial notching is usually seen in patients with horizontal growth pattern where orofacial muscular forces are strong.…”
Section: Introductionmentioning
confidence: 99%
“…12 Different studies have been conducted so far on finding out the frequency of lower third molar impactions and its pattern in different populations. 9,10 However few studies have been reported on the frequency of lower third molar impactions in patients with different morphological characteristics. To our knowledge, this is the first study aimed at determining the frequency of impacted lower third molars in orthodontic patients with different antegonial notch depths.…”
Section: Introductionmentioning
confidence: 99%